04.11: Strength enhancement in axially compressed cylinders with stepped walls. (13th September 2017) - Rotter, J. Michael; Al Lawati, Hussain
ABSTRACT: Metal silos and tanks are subject to loading that increases progressively from the top to the base of the cylindrical shell. Efficient design calls for progressive increases in wall thickness, but metal sheets are made in discrete thicknesses. For silos, buckling under axial compression is the dominant design condition, whilst in tanks axial compression with internal pressure may also be critical. The step increases in wall thickness mean that the most critical point on the wall is always at the base of one strake of uniform thickness, so the location of a critical buckle is expected to be at or just above a change of thickness. Until now, design rules have always ignored the effect of the thicker lower strake in restraining the axial compression buckle above it, and the requirement for buckles to have a finite size. Whilst this effect has previously been noted [1, 2], it has never been systematically studied. In this paper, a first thorough study is presented, which shows that the strength enhancement associated with a change of plate thickness can be considerable (over 40%). The presented information addresses the buckling of imperfect shells, and includes both elastic and plastic conditions. The findings are sufficient to produce a modification of the current design rules for buckling under axial compression, giving designers the freedom to extend their thin shell segments deeper in the silo or tank structure.